Seroprevalence of Cryptosporidium parvum and Neospora caninum in cattle in the southern Kyushu region of Japan. Issue 6 (December 2018) - Masatani, Tatsunori; Fereig, Ragab M.; Otomaru, Konosuke; Ishikawa, Shingo; Kojima, Isshu; Hobo, Seiji; Nishikawa, Yoshifumi
Abstract: Cryptosporidium parvum and Neospora caninum are common parasites in domesticated cattle worldwide, including in Japan. We carried out a serological survey to detect C. parvum and N. caninum infection among cattle in the southern Kyushu region of Japan—including the small islands—by indirect enzyme-linked immunosorbent assay based on recombinant antigens. We found that total seropositivity in 570 Japanese black cattle was 96.3% for C. parvum and 18.4% for N. caninum . Although seroprevalence was correlated with cattle age, differences in the seroprevalence of C. parvum among age groups were not statistically significant. On the other hand, N. caninum seroprevalence increased with age, suggesting horizontal transmission through ingestion of food or water contaminated with oocysts. These findings underscore the importance of monitoring C. parvum and N. caninum in cattle and implementing measures to prevent the spread of infection to other livestock and to humans.